Beyond Single Exposure: Recycled Input and Vocabulary Mastery in Young EFL Learners - Salsa Aulini; Kalsum Kalsum; Nanning Nanning; Munawir Munawir (Hasanuddin University, 2026)
Vocabulary mastery constitutes a foundational pillar in English language learning for young learners at Islamic elementary schools (Madrasah Ibtidaiyah/MI). However, linear and non-repetitive vocabulary instruction frequently constrains learners from achieving adequate vocabulary mastery. This study investigates the effectiveness of the Recycled Input Technique (RIT) operationalized through four sequential stages exposure, retrieval, recycling, and consolidation on the vocabulary mastery of Grade IV students at MI DDI Ujung Lare Parepare. Employing a pre-experimental design with a one-group pretest–posttest model, this study selected 25 students with complete paired data from a total enrolment of 28 fourth-grade students through simple random sampling. The target vocabulary comprised 20 items from the Daily Activities unit of the My Next Words Grade 4 textbook. The assessment instrument consisted of a 20-item vocabulary test covering multiple-choice, word-matching, and sentence-completion tasks. Data were analyzed using descriptive statistics and a paired-samples t-test. The analysis revealed a mean score improvement from 73.80 in the pretest to 93.20 in the posttest, a gain of 19.40 points, with t(24) = 7.41, p < .001, and a large practical effect (Cohen's d = 1.48). The proportion of students achieving the 'Excellent' category rose from 8% to 80%, while the 'Poor' category was completely eliminated, decreasing from 20% to 0%. These findings substantiate that systematically designed recycled input significantly enhances vocabulary mastery in EFL contexts at the Islamic primary school level, with particularly pronounced gains observed among initially low-performing learners.